Mediators of Socioeconomic Inequity in Living-donor Kidney Transplantation: Results From a UK Multicenter Case-Control Study. Issue 4 (April 2020) - Bailey, Pippa K.; Caskey, Fergus J.; MacNeill, Stephanie; Tomson, Charles R.V.; Dor, Frank J.M.F.; Ben-Shlomo, Yoav
Abstract : Background: There is evidence of socioeconomic inequity in access to living-donor kidney transplantation, but limited evidence as to why. We investigated possible mediators of the inequity. Methods: This questionnaire-based case-control study included 14 UK hospitals. Participants were adults transplanted between April 1, 2013 and March 31, 2017. Living-donor kidney transplant (LDKT) recipients (cases) were compared with deceased-donor kidney transplant recipients (controls). We collected data on mediators identified in earlier qualitative work: perceived social support (Interpersonal Support Evaluation List shortened version-12), patient activation (Patient Activation Measure 13), and LDKT knowledge (Rotterdam Renal Replacement Knowledge Test). We performed mediation analyses to investigate what proportion of the effect of socioeconomic position (education and income) on case-control status was mediated by these variables. Results: One thousand two-hundred and forty questionnaires were returned (40% response). Receipt of an LDKT over a deceased-donor kidney transplant was associated with higher socioeconomic position [adjusted odds ratio (aOR) university degree versus no degree aOR = 1.48 (95% confidence interval [CI], 1.18-1.84), P = 0.001 and aOR per +£1000 increase in monthly household income after tax 1.14 (95% CI, 1.11-1.17), P < 0.001] higher perceived social support (aOR per +1-point Interpersonal Support Evaluation List shortened version-12 score = 1.05 (95% CI, 1.03-1.08), P < 0.001), higher levels of patient activation (aOR per +1 patient activation measure level = 1.35 (95% CI, 1.24-1.48), P < 0.001), and greater LDKT knowledge (aOR per + 1-point Rotterdam Renal Replacement Knowledge Test score = 1.59 (95% CI, 1.49-1.69), P < 0.001). Mediation analyses revealed that perceived social support, patient activation, and LDKT knowledge together mediate 48.5% (95% CI, 12.7-84.3, P = 0.008) of the association between university education and LDKT status, and 46.0% (95% CI, 28.7-63.4, P < 0.001) of the association between income and LDKT status. Conclusions: LDKT knowledge, perceived social support, and patient activation are associated with the socioeconomic position of people with kidney disease, and mediate approximately 50% of the association between the socioeconomic position and receipt of an LDKT. Interventions that target these factors may redress observed socioeconomic inequity. Abstract : Supplemental Digital Content is available in the text.